Key Sectors in the Economy of Saudi Arabia - Said K. M. Brika; Said K. M. Brika; Brahim Adli; Khalil Chergui (Frontiers Media S.A., 2021)
This study shows the key sector for the economy of Saudi Arabia based on input-output model analyses. They derived the analyses from the economy of the Kingdom of Saudi Arabia (KSA) using 35 economic sectors. We found that four leading sectors exceeded the values of the linkage coefficients with a value of 1, represented by both chemicals and pharmaceutical products, namely, manufacturing basic metals (S13), transportation and storage (S24), and other business sector services (S31). According to the unbalanced growth theory, more attention is paid to these sectors that are the primary engine for the rest of the sectors and their growth. The results obtained are beneficial for success of the economic policy of Saudi Arabia. By observing the different influences, it is possible to identify the policies expected to have more significant indirect impacts on other sectors in Saudi Arabia and are likely to develop a prudent economic policy. Given the economic dependence on oil, it is also essential to be acquainted with the different sectors that are probable to have an overall effect on the economy for strategic and operationally effective analysis that can help.